LEARNING WRITING IN PRIMARY SCHOOL (Qualitative Study- Ethnography in SD Islam Jerapah Kecil Jakarta Timur) - Gusti Yarmi (Bahtera: Jurnal Pendidikan Bahasa dan Sastra, 2016)
The aims of this study is to determine the understanding of the application of learning to writing inIslamic Primary School Jerapah Kecil. This study is a qualitative study using ethnographicmethods by Spredly models. This study was conducted in March-July 2013. The results of thisstudy indicate that the teaching of writing in Islamic Primary School jerapah kecil has a uniqueassociated with writing learning objectives, which expects students have writing skills through thepractice of writing contextually and directing the students how student happy and loved to writing.Through writing activities teachers can instill a positive attitude to the students. In this study itwas found that the approach used in the teaching of writing in addition to using thecommunicative approach and whole language is also very good on student-centered learning.Writing skills of students trained through various activities at the school. Writing activitiesperformed in the morning activities, the process of learning activities and activities by schoolprogram. Writing a journal is a routine activity conducted in the morning activities in order totrain skilled student and enjoys writing. Various program activities outside of school in order tostimulate various aspects of development and potential students, including writing. Assessmentthat teachers do, not just results-oriented, but also the process. Then the aspects that not only thecognitive aspects but also aspects of the attitude or character cultivation. Utilizing a variety oflearning resources one museum as a learning resource writing to develop positive attitudes instudents through writing activities. Penelitian ini bertujuan untuk mengetahui pemahaman mengenai penerapan pembelajaran menulisdi Sekolah Dasar Islam Jerapah Kecil. Penelitian ini adalah penelitian kualitatif denganmenggunakan metode etnografi model Spredly. Penelitian ini dilaksanakan pada bulan Maret-Juli2013. Hasil penelitian ini menunjukkan bahwa pembelajaran menulis di Sekolah Dasar IslamJerapah Kecil memiliki keunikan yang berkaitan dengan tujuan pembelajaran menulis, yaitumengharapkan siswa memiliki keterampilan menulis melalui praktek menulis secara kontekstualdan lebih mengarahkan pada siswa bagaimana siswa senang dan gemar menulis. Melalui kegiatanmenulis guru dapat menanamkan sikap positif pada diri siswa. Dalam penelitian ini ditemukanbahwa pendekatan yang digunakan dalam pembelajaran menulis selain menggunakan pendekatankomunikatif dan whole language juga sangat ditekankan pada pembelajaran yang berpusat padasiswa. Keterampilan menulis siswa dilatih melalui berbagai kegiatan yang ada di sekolah.Kegiatan menulis dilakukan pada kegiatan pagi, pada proses kegiatan pembelajaran dan kegiatanprogram sekolah. Menulis jurnal merupakan kegiatan rutin yang dilakukan pada kegiatan pagidalam rangka melatih siswa terampil dan gemar menulis. Memprogramkan berbagai kegiatan diluar sekolah dalam rangka menstimulasi berbagai aspek perkembangan dan potensi siswatermasuk menulis. Penilain yang dilakukan guru tidak hanya berorientasi pada hasil tetapi jugaproses. Kemudian aspek yang dinilai tidak hanya aspek kognitif namun juga aspek sikap ataupenanaman karakter. Memanfaatkan sumber belajar yang bervariasi salah satunya museum sebagaisumber belajar menulis yang dapat mengembangkan sikap positif pada siswa melalui kegiatanmenulis.